Research on Prediction and Prevention Technology of Mine Water Disaster - Wang, Runmin; Fang, Yudong; Liu, Siyi (International Journal of Natural Resources and Environmental Studies, 2026)
Mine water disaster is a common safety hazard in the process of coal mining, which poses a major threat to the life safety of miners and coal mine production. Major safety and environmental problems in the process of mining. With the continuous increase of mining depth, the difficulty of mine water prevention and control is also increasing. This paper first expounds the types and hazards of mine water disaster and the current situation, problems and development trend of mine water prevention and control, and then analyzes in detail the common methods of water disaster prediction, including geological exploration, hydrogeological investigation, hydrological simulation, remote sensing technology, etc., and compares the advantages and disadvantages of each method. Finally, the measures of mine water disaster prevention and control are discussed, including mining design, hydrological control, precipitation and drainage, water plugging and water control, etc., and the application effect of prevention and control measures is analyzed with specific cases.